Relationships between cornell musculoskeletal discomfort questionnaire and online rapid office strain assessment questionnaire - Shariat, Ardalan; Cleland, Joshua A.; Danaee, Mahmoud; Kargarfard, Mehdi; Moradi, Vahide; Mohd Tamrin, Shamsul Bahri (Tehran University of Medical Sciences, 2018)
Background: The Rapid Office Strain Assessment (ROSA) is a tool employed online to screen office workstations, which may require modification to decrease musculoskeletal discomfort of workers. This study aimed to examine if the ROSA is able to evaluate pain severity in the lower back, shoulder and neck of office workers accurately. Methods: Overall, 142 participants (height: 1.80 ± 0.15 m, BMI: 26.08± 6.70, age: 35±15 yr) with at least a year of working experience completed both questionnaires, the online ROSA and the Cornell musculoskeletal discomfort, in 2016 in Malaysia. Results: Relationship between the total scores of both questionnaires for lower back, shoulder and neck pain were significant but exhibited a weak to moderate relationship (range of r values from 0.012 (CI 95%, −0.153–0.176) to 0.503 (CI 95%, 0.369–0.616). Conclusion: The online ROSA does not appear to be a reasonable tool for evaluating the severity of lower back, shoulder and neck pain among office workers as the correlations were low. We suggest continued use of the musculoskeletal discomfort questionnaire. Additional studies are required to further examine the ROSA for other anatomical regions.